TEFSIRU'L -AYATI'L-AHKAM FI KITABI'L-MEBSUT LI İMAMI'-SERAHSI MIN SURETI'L-AHKAF ILA SUREI'T-TALAK - JALAL, KHASRAW SAMAD (Fırat Üniveristesi, 2017)
İlimlerin en yücesi tefsir ilmidir. Bu ilmin dallarından biri de Allah'ın Kitabındaki ayetlerden şer'î hüküm veya fıkhî kâide elde eden tefsîr-i teşrîi ilmidir. Gerek eski gerekse de yeni âlimler bu ilme önem vermişlerdir, Malumdur ki, İslâmî teşrî'de/hüküm koymada Kur'ân-ı Kerîm, esas ve ilk kaynaktır. Şer'î hükümler, Kur'an ve Nebevî sünnete bina edilirler. Kur'an, Teşrîi kaynakların esası ve direği olunca; haliyle Tefsir ve Kur'an'dan hüküm istinbat etmek de, ilimlerin en kıymetlisi ve en yücesi olur. Çünkü bu ilim, hayat için gerekli olan şer'î, amelî hükümleri ele alır. Kuşkusuz, ahkâm âyetlerini bilmenin genelde bütün Müslümanlar; özelde de tefsir ve fıkıh araştırmacısı için büyük faydaları vardır. Çünkü onları bilmek, Alah'ın insanlar için teşri' buyurduğu şeyleri bilmenin yegâne yoludur. Onlarla helali-haramı bilir ve yine onlarla Allah'ın bize vacip veya müstehap gördüklerini temyîz ederiz. Çünkü onlar, kulların dünya ve ahiret maslahatlarına dair fıkhî hükümleri içeren âyetlerdir. tezimde Kur'an'ın son cüzlerinde geçen bazı ahkâm âyetleri hakkında; İmam Serahsî'nin hanefî fıkıh kitaplarının en büyük ve en önemlilerinden olan Mebsut isimli kitabındaki değerlendirmelerini ele aldım.

The greatest science is the explanation science, and one of the branches of this science is the legislative explanation that takes a legitimacy rule or a jurisprudential rule from the verses of the Book of God, the scientists took care of this science recently and in the past, it is known from the religion necessarily that Quran is the main source of the first and the first Islamic legislation, And the Sharia rules have built on Quran and Sunnah, and due to Quran is the base of these sources and pillar, work on it and explanation of its rulings are the most dangerous sciences, and due to deal with Sharia rulings in daily life. There is no doubt that the knowledge of the verses of the rulings has great benefits for all the Muslims, especially for the explanative and jurisprudential researcher, because knowing of them is the way to know what God has revealed to people, we know the haraam (unallowed) and halal (allowed), and distinguish what God has enjoined on us and what he desired, because the verses include rulings that relate to interests of people in life and hereafter. Therefore, I discussed in my dissertation some rulings verses in the last parts of Quran, which was considered by Imam Sarkhasy, God belles him, the verses of rulings and he referred in his book Almabsoot, which is one of the greatest books of Hanafi jurisprudence and the largest.
İmami'-Serahsinin Mebsutinda ahkam ayatlerinin tefsiri (Ahkaf – Talak sureleri)
Keywords: Din